THE INFLUENCE OF SOCIAL MEDIA MARKETING ON INTENTION TO ENROLL MEDIATED BY CONSUMER BRAND ENGAGEMENT, BRAND AWARENESS, AND BRAND IMAGE IN PRIVATE UNIVERSITIES IN JAKARTA AND TANGERANG - Imanuel Xaverdino Wiratama Pasaribu; Hendra Achmadi (Transpublika Publisher, 2024)
This study explores the influence of Social Media Marketing on Intention to Enroll, mediated by Consumer Brand Engagement, Brand Awareness, and Brand Image at private universities in Jakarta and Tangerang. Data were collected from 175 respondents through a questionnaire and analyzed using the SEM PLS method. The results showed that Social Media Marketing has a significant positive influence on Consumer Brand Engagement, Brand Awareness, Brand Image, and Intention to Apply. Effective social media marketing is able to increase consumer engagement with the university brand, which is reflected in increased interaction, loyalty, and support for the brand. In addition, active social media marketing activities and relevant content were shown to increase prospective students' intention to enroll in private universities, making it an effective tool in influencing prospective students' decisions. The study also found that social media marketing increases brand awareness, allowing universities to reach more prospective students and establish more effective communication. Effective use of social media can strengthen brand image and build closer relationships with consumers. High consumer engagement with the brand increases brand awareness and a positive brand image, which contributes to an increased desire to enroll. Overall, this study emphasizes the importance of social media marketing strategies in increasing consumer engagement, brand awareness, brand image, and intention to enroll in private universities, especially in the post-pandemic context.